Penentuan Harga Transfer: Harmoni antara Regulasi Pajak, Sistem Manajemen Biaya, dan Kepentingan Pemangku Kepentingan - Butarbutar, Melati (Universitas Dehasen Bengkulu, 2025)
Transfer pricing represents a strategic element within multinational enterprises as it lies at the intersection of tax compliance, cost management systems, and the interests of multiple stakeholders. This study synthesizes findings from ten selected journals that examine the determinants of transfer pricing, the methods used to establish transfer prices, and the implications for taxation and corporate governance. The synthesis reveals that firm size, foreign ownership, leverage, and tunneling incentives are the most consistent factors influencing transfer pricing practices. From a managerial perspective, the Activity-Based Costing (ABC) method enhances the accuracy of transfer price determination compared to traditional costing approaches. Meanwhile, from a taxation standpoint, the application of the arm’s length principle through the Comparable Uncontrolled Price (CUP), Cost Plus, and Profit Split methods remains the most relevant approach to minimizing the risk of cross-border tax disputes. This study concludes that achieving balance among tax regulations, appropriate cost management systems, and effective corporate governance mechanisms is crucial for ensuring that transfer pricing practices are conducted fairly, transparently, and accountably.